Birds - Meadway, Wendy (New York : Bookwright Press, 1990)
An introduction to the types, characteristics, habits, and behavior of birds.
Includes bibliographical references (p. 31) and index.
3.9
K-3
Keywords: Birds -- Juvenile literature; Birds; Birds